Analisis Kadar Mineral dalam Abu Buah Nipa (Nypa fructicans) Kaliwanggu Teluk Kendari Sulawesi Tenggara - Herman Herman; Rolan Rusli; Edi Ilimu; Rimba Hamid; Haeruddin Haeruddin (Journal of Tropical Pharmacy and Chemistry, 2011)
Research about Levels of ash analysis in Nipa Fruit (Nypa fructicans) Kaliwanggu Kendari Gulf South East Sulawesi have been done. Research carried out by gravimetric method and AAS. The ash content of old nipa fruit at a temperature 450Â°C dan 550Â°C obtained amounted to 1.01% and 0.89%. while the young nipa fruits obtained ash content of 0.88% and 0.86% at450Â°C dan 550Â°C. Mineral content of old nipa fruit which had become ash at a temperature of 450Â°C obtained at 1.3769 ppm, 7.9167 ppm, 3.7876 ppm, 9.2365 ppm, respectively for Fe, Mg, K, and Na. On the other hand, at a temperature of 550Â°C obtained at 1.1153 ppm, 8.0127 ppm, 3.7990 ppm and 9.3634 ppm, respectively for Fe, Mg, K, and Na. On young fruit nipah obtained concentration of 0.8769 ppm, 7.9939 ppm, 3.8260 ppm, 9.4041 ppm, respectively for Fe, Mg, K, and Na at ash temperature 450Â°C. Meanwhile, at a ash temperature of 550Â°C obtained concentration of 0.9230 ppm, 7.9738 ppm, 3.7468 ppm and 9.3861 ppm, respectively for Fe, Mg, K, and Na. The water content obtained from the old and young nipa flesh fruit obtained at 41.86% and 33.49%, respectively. Key words: Level of mineral analysis, Nypa fructicans, Gravimetric, AAS ABSTRAK Telah dilakukan penelitian dengan judul â€œAnalisis Kadar dalam Abu Buah Nipa (Nypa fructicans)â€ Kaliwanggu Teluk Kendari Sulawesi Tenggara. Penelitian dilakukan dengan metode gravimetri dan AAS. Kadar abu buah nipa tua pada suhu 450Â°C dan 550Â°C diperoleh sebesar 1,01% dan 0,89%, sedangkan pada buah nipa muda diperoleh kadar abu sebesar 0,88% dan 0,86% berurut-turut untuk suhu 450Â°C dan 550Â°C. Kadar mineral buah nipa tua yang diabukan pada suhu 450Â°C diperoleh sebesar 1,3769 ppm, 7,9167 ppm, 3,7876 ppm, 9,2365 ppm, berturut-turut untuk Fe, Mg, K, dan Na. Sedangkan pada suhu 550Â°C diperoleh sebesar 1,1153 ppm, 8,0127 ppm, 3,7990 ppm, dan 9,3634 ppm, berturut-turut untuk Fe, Mg, K, dan Na. Pada buah nipa muda diperoleh kadar sebesar 0,8769 ppm, 7,9939 ppm, 3,8260 ppm, 9,4041 ppm, berturut-turut untuk Fe, Mg, K, dan Na pada suhu pengabuan 450Â°C. Sedangkan pada suhu pengabuan 550Â°C diperoleh kadar sebesar 0,9230 ppm, 7,9738 ppm, 3,7468 ppm, dan 9,3861 ppm, berturut-turut untuk Fe, Mg, K, dan Na. Adapun kadar air yang diperoleh dari daging buah nipa tua dan muda diperoleh sebesar 41,86% dan 33,49%. Kata kunci: Analisis kadar mineral, Nypa fructicans, Gravimetri, AAS